Effectiveness of an e-portfolio-based writing method using analytic traits on writing performance of EFL students - Azarfam, Aliasghar Yousefi (2016)
This study focused on the writing skill development of EFL learners by examining the effect of an alternative method of writing instruction on the writing ability of Iranian university students in a public Malaysian university. The writing method introduced and implemented in this study was developed based on the four dimensions of process, genre, electronic portfolios, and analytic traits of writing. The integration of these elements into the writing instruction was the main purpose of this study in order to make improvement in the writing skill of the EFL learners. In EFL writing instruction and in writing portfolios, learners are required to do writing assignments without being actually shown the writing process and the analytic qualities of writing. Even in ‘Process’ model of writing, or in writing e-portfolios, learners are asked to be involved in the writing process through peer- and self-assessment, but they are not given any specific criteria or scale to do so. At the same time, although instructors evaluate learners’ writing drafts, they seldom do so in a way to guide instruction in the writing process or reflect all traits of the writing. In this study, an ‘explanatory design’ was used to appraise the effectiveness of the writing e-portfolio method using analytic traits. Hence, the data were sequentially collected by first collecting the major and prior quantitative data through conducting an experimental study. The qualitative data, acquired through semi-structured interview, were then used to support the results from the quantitative data. The reason for choosing a quantitative study was to obtain empirical data and to see if a significant effect size was observed by applying the new method. The results from qualitative interview, on the other hand, helped to identify unobserved heterogeneity in quantitative data and shed light on them. It was used to grasp the attitudes of learners in order to get deeper into the effect of e-portfolio models on the writing ability of students, which may have been unnoticed in the quantitative part of the study. The selected sample for the study was randomly assigned to two Experimental Groups and one Control Group. The reason to include two treatment groups was the incorporation of online learning system and analytic traits of writing as two levels of independent variable – i.e. ‘method’ in this study. Hence, the learners in Writing E-portfolio 1 (WE1) were required to make use of an online Learning Management System or LMS in addition to the analytic traits of writing, but the learners in Writing E-portfolio 2 (WE2) were just introduced to LMS without being presented with the analytic traits of writing. At the same time, the members of Writing Portfolio (WP) were asked to follow the procedure of the classic writing portfolio making no reference to LMS or writing analytic traits. The teaching and learning strategies in WE1 were based on the Process Scale of Akef and Maftoon (2010), and involved self-, peer-, and teacher-assessments. The instructor used the scale itself in the process of writing, but the learners used a simplified and adapted checklist as Peer Checklist for reviewing and commenting on the writing drafts of their peer-group members. The results of the research showed that although the documented difference between the two treatment groups – WE1 and WE2 – was not significant in this study, the experiences and expressions of the learners showed a difference in the attitudes of them towards the analytic traits of writing. The learners in WE1 talked about a sort of awareness of the different qualities of writing. They claimed that knowing about the analytic traits of writing caused them to understand and be convinced that they need to pay attention to all aspects of writing and not just the usage and mechanical correctness of it. It was a new look at writing ability causing the learners to pay attention and be sensitive to these required features of writing. The learners in WE1 referred to the role of Peer Checklist in reminding them of the writing qualities to be considered in their self- and peer-assessment. Nevertheless, the learners in both treatment groups referred to the relative benefits, compatibility, observability, trialability, and complexity of the introduced methods in the LMS environment. As it was the first experience of most of the learners in dealing with the electronic portfolios in LMS and the analytic qualities of writing, they were more motivated to be involved in the course activities. The learners in WE1 were, therefore, expected to have much better writing performance by the course instructor. However, because of encountering some complexities and being inexperienced in dealing with the new environment, the learners in WE1 could not show ideal writing performance; nevertheless, the respondents of WE1 were mainly satisfied with the learning strategies they learned and applied in the course. It was found very crucial to scaffold the writers and provide them with a framework and a pattern to know what to do and how to cover the different stages of writing following the method instructions. Additionally, in this study, the electronic environment of e-portfolios proved to play a significant role in facilitating the writing task performance of the learners and consequently improving their writing skill in both WE1 and WE2 groups. The gained quantitative and qualitative findings of this study proved to be satisfactory in terms of the impact of online environment on the writing performance of the learners in comparison with the writing performance of WP or Control group. The significant difference was observed in comparing both the total gained scores of the learners and the obtained scores of the learners in certain traits of writing. It meant that the electronic environment of portfolios was an effective means to facilitate the writing activities and help the EFL learners to achieve their desired goals through making improvement in their own writing.